Adapting Road Procurement to Climate Conditions - Iimi, Atsushi (World Bank, Washington, DC, 2012)
The world's climate is changing. It is well recognized that technical standards and project specifications of public infrastructure have to be adjusted, depending on the climate. However, it is less recognized that the public infrastructure procurement also needs to be adjusted. This paper examines a particular case of rural road procurement in Nepal. Severe weather conditions, such as heavy rains and storms, are likely to interrupt civil works and wash away unpaved or gravel roads. It is found that heavy precipitation causes delays, but not cost overruns. The paper also shows that budgetary efficiency and credibility could be improved by taking climate conditions into account. If future precipitation were anticipated by backward-looking expectations, many large project delays could be avoided. If the autoregressive precipitation model were used, the vast majority of the observed delays could be eliminated.